2004
DOI: 10.1016/s1534-5807(03)00402-7
|View full text |Cite
|
Sign up to set email alerts
|

The Atg1-Atg13 Complex Regulates Atg9 and Atg23 Retrieval Transport from the Pre-Autophagosomal Structure

Abstract: To survive extreme environmental conditions, and in response to certain developmental and pathological situations, eukaryotic organisms employ the catabolic process of autophagy. Structures targeted for destruction are enwrapped by double-membrane vesicles, then delivered into the interior of the lysosome/vacuole. Despite the identification of many specific components, the molecular mechanism that directs formation of the sequestering vesicles remains largely unknown. We analyzed the trafficking of Atg23 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
592
5
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 439 publications
(638 citation statements)
references
References 37 publications
33
592
5
8
Order By: Relevance
“…The PI3P-binding protein Atg18/WIPI and its binding partner Atg2 are recruited to such a platform. Although the exact function of Atg2-Atg18/WIPI in autophagosome biogenesis is not clear, it has been shown that the Atg2-Atg18 complex is required for normal distribution of Atg9 vesicles [38][39][40].…”
Section: The Atg1/ulk Complexmentioning
confidence: 99%
“…The PI3P-binding protein Atg18/WIPI and its binding partner Atg2 are recruited to such a platform. Although the exact function of Atg2-Atg18/WIPI in autophagosome biogenesis is not clear, it has been shown that the Atg2-Atg18 complex is required for normal distribution of Atg9 vesicles [38][39][40].…”
Section: The Atg1/ulk Complexmentioning
confidence: 99%
“…18,19 Atg9 is the only currently characterized transmembrane protein involved in the formation of double-membrane vesicles, and is thought to mark membranes to be donated to the PAS. 20 Atg1 regulates the shuttling of Atg9 between the PAS and a peripheral pool and in this way is thought to control retrieval of Atg9 and the associated membrane 20 (Figure 2). …”
Section: Macroautophagy In Yeast Is a Multistep Process That Is Regulmentioning
confidence: 99%
“…Atg13 and Atg1 also form a complex with Atg17, which is involved in regulating the size of the vesicles during autophagy. 27,28 Another way that Atg1p differentially regulates the cvt and autophagy pathways is through the recycling of Atg9p and/or Atg23p (a peripheral membrane protein) depending on the kinase activity of Atg1p 20 . Similar to Atg11, Atg23 is essential for cvt.…”
Section: Macroautophagy In Yeast Is a Multistep Process That Is Regulmentioning
confidence: 99%
“…One of the most intriguing questions is the origin of the membrane for the double-membrane Cvt vesicles or autophagosomes. Recent data suggest that Atg9 may mark the membrane that is donated to the forming sequestering vesicles (Noda et al, 2000;Reggiori et al, 2004a). Atg9 localizes to mitochondria and cycles between this compartment and the pre-autophagosomal structure (PAS), the site of organization for Cvt vesicle and autophagosome formation (Tucker et al, 2003).…”
Section: Introductionmentioning
confidence: 99%